Effect of organic manures and NPK levels on yield and quality of Bottle gourd [Lagenaria siceraria (Mol.) Standl.] (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted during kharif, season of 2012 to study the effect of organic manures and NPK levels on Bottle gourd. The experiment consisted 16 treatment viz., Four levels of NPK (control, 100:50:50, 80:40:40 and 60:30:30) and organic manures (control, vermicompost, poultry manure and FYM) factorial RBD with three replications. Results indicated that the application of NPK (100:50:50) + vermicompost (5.0 t ha') remaining at par with dose of NPK (80:40:40) + vermicompost (5.0 tha"), exhibited maximum per cent fruit set, number of fruit per vine, fruit length, fruit weight, total yield per vine, total yield, protein content in fruit and crude fiber content in fruit.
Keywords: application; organic manures; vermicompost; crude